The Conflict Between The Two Parts Of Yemen And The Position Of The University Of Arab States On It Between The Years 1972-1978 (Journal of the College of Basic Education, 2024)
The conflict between the two parts of North and South Yemen is one of the important issues that were brought to the table of the League of Arab States in the seventies of the last century. The League of Arab States sought, by sending many delegations to the two parts of North and South Yemen, to find appropriate solutions to that conflict. The border dispute was general. 1972 was one of the most severe border disputes presented to the Arab League. The Arab League was able to resolve it for the period between 1972-1973. To settle all conflicts and conclude the Cairo Agreement and the Tripoli Statement. They set the conditions for Yemeni unity and laid the foundations for stability under the umbrella of the League of Arab States. The renewal of conflicts between the two parts of Yemen for the period between 1974-1978 and the accompanying assassinations of political leaders in the northern part of Yemen and the exchange of accusations between the two parts affected the cessation of unity talks and the issuance of the strongest decisions. From the League of Arab States since its founding, which represented the freezing of South Yemen’s membership in the League of Arab States and the severing of political, economic and cultural relations between the Arab League countries and South Yemen.